THE IMPACT OF WORD OF MOUTH AND BRAND IMAGE ON BUYING DECISIONS OF ZOMATO GOLD’S MEMBERSHIP - Nesya Nada (Bina Nusantara University, 2020)
In January 2020, Zomato Gold has around +1500 restaurant partners in JABODETABEK within total members +100.000. Zomato gold focuses on the FNB world, where other competitors have beneficial besides FNB such as spa, fitness, salon. It aims to stay in the FNB corridor. The purpose of this study is to investigate the Impact Word of Mouth and Brand Image on Buying Decisions. The objective of this research is the sales of Zomato Gold’s membership affected the variables, by obtained samples from the questionnaire results of 102 active users of Zomato Gold. Simultaneous test results (F) showed a significance value (p-value) smaller than the alpha value of 0.000 <0.05. The effect of the two variables on the Buying Decision is 43.3% while the remaining 56.7% represents the influence of other variables. Thus, companies need more focus on Brand Image, improve their services on Zomato Gold, it can affect the impact of variable WOM more positively.